The Effect of English Language Speech Assistant (Elsa) Application on Improving Students' Speaking Skills - Putri, Mega; Nurkamilah; Hanafi (Institut Agama Islam Tarbiyatut Tholabah, 2024)
This research aims to find out whether using the Elsa Application in learning English can improve the speaking skills of grade 8 students at SMPN 8 Jember. This research focused on pre-experimental research in one class pre-test and post-test. The population of this research is grade 8 students at SMPN 8 Jember in the 2023/2024 academic year, consisting of 224 students. The researcher took one class as a research sample, namely class 8 which consisted of 32 students. Data was obtained from speaking ability tests when retelling stories in the pre-test and post-test. It can be concluded that the results of this study show that the use of the Elsa application can improve students' speaking skills which include grammar, comprehension, pronunciation, vocabulary, and fluency. This can be seen in the students' average score on the pre-test, which was 60 and increased to 75.5 on the post test. This means that using the Elsa application in learning English can improve the speaking skills of grade 8 students at SMPN 8 Jember.